2004
DOI: 10.1002/ceat.200401960
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Oxygenation Improvement by Interaction of Bubbles and Vibration Fields

Abstract: Gas bubble motion characteristics and bubble size are important factors in various technological processes involving the interaction between liquid and gaseous systems. The present work studies the effect of vibration fields on the characteristics of bubble motion and bubble size. Bubble retention time in the liquid (rise velocity) and bubble mean diameter were chosen as main parameters effecting the oxygen mass transfer rate. A device for mechanical vibration of the aerated liquid was used. The influence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…where Re study [11] were used to obtain the values of this variable. The number of bubble up and down movements k were measured experimentally and varied from 2 to 30 for the applied range of vibration frequencies and amplitudes.…”
Section: Theoretical Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…where Re study [11] were used to obtain the values of this variable. The number of bubble up and down movements k were measured experimentally and varied from 2 to 30 for the applied range of vibration frequencies and amplitudes.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…The number of bubble up and down movements k were measured experimentally and varied from 2 to 30 for the applied range of vibration frequencies and amplitudes. Bubble velocity was calculated by equations obtained in a previous study [11].…”
Section: Theoretical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present research, a vibrating plate suggested in previous studies [6,7] is used, but here it is located sufficiently close to the liquid surface. Vibrations of the plate generate gas bubbles and entrain them into the liquid.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of vibrations on gas bubble behavior in liquids was investigated theoretically and experimentally in various studies [5][6][7]. It was shown theoretically that when a small bubble is placed in a vertically vibrating liquid, it is subjected to a downward force which opposes the buoyancy force due to gravity.…”
Section: Introductionmentioning
confidence: 99%